PENGARUH PEMASARAN RELASIONAL DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN HOTEL SAFARI LABUHANBATU UTARA - Bati Bati (JURNAL PIONIR, 2019)
Relational marketing and service quality towards customer loyalty of the Hotel Safari Labuhanbatu Utara ". The analytical method used is descriptive analysis method and statistical analysis method. Data collection techniques are interviews, questionnaires and study documentation. The formulation of the problem in this research is to find out and analyze whether there is an influence of relational marketing and service quality on customer loyalty at the Labuhanbatu Utara Safari Hotel. The result of the determinant coefficient (R2) is 0.674 which means that the Relational Marketing and Service Quality variables have a close relationship with Customer Loyalty (Y) at the Labuhanbatu Utara Safari Hotel. Adjusted R Square of 0.440 means the value of 44% increase in Customer Loyalty (Y) at the Labuhanbatu Utara Safari Hotel can be explained by Relational Marketing and Service Quality, while the remaining 66% can be explained by other variables not examined in this study.Keywords: Relational Marketing, Service Quality, and Loyalty Customer.